PENGARUH PEMBERIAN LIMBAH KOPI TERHADAP PERTUMBUHAN TANAMAN SELADA (Lactuca sativa L.) - Nimas Disri Putri; Endah Dwi Hastuti; Rini Budi Hastuti (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2017)
Lettuce plant is one of type of vegetable plant that has a high nutrient content consisting of protein, fat carbohydrates, calcium, and vitamins. Lettuce production in Indonesia has increased due to high demand of lettuce on the market. High production is supported by the high cultivation of lettuce. This high lettuce cultivation affects the use of fertilizer, where inorganic fertilizers are more widely used today. The use of inorganic fertilizers should be reduced because of its negative impact on the environment. Organic fertilizer is an appropriate solution to reduce the use of inorganic fertilizers. One of the materials that can be used as organic fertilizer is coffee waste.Coffee waste contains one of the essential nutrients in plant growth that is Nitrogen. This study aims to analyze that effect of solid and liquid coffee waste on the growth of lettuce plants (Lactuca sativa L.). The research was conducted by using Completely Randomized Design (RAL) with single factor that is the concentration of coffee waste. The study consist of 7 treatments, namely 0g/kg of coffe waste, 10g/kg of solid waste,20g/kg of solid waste, 30g/kg of solid waste, 10g/100ml of liquid waste, 20g/100ml of liquid waste, and 30g/100ml with 5 repetitions. The parameters observed were plant height, leaf number, wet weight and dry weight of plant, root length, wet weight and dry weight of root,. Data analysis using ANOVA followed by Duncan’s Multiple Range Test at 95% confidence level. The results showed that coffe waste significantly affected and improved the growth of lettuce (Lactuva sativa L.). Liquid waste concentration 10g/100ml gives the best result to the growth of lettuce plant (Lactuca sativa L.). Key words: lettuce, Lactuca sativa L., coffe waste